2014
DOI: 10.1080/15564894.2014.880759
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical Characterization of Lapita Ceramics From the Western Solomon Islands by Means of Portable X-Ray Fluorescence and Scanning Electron Microscopy

Abstract: International audienceThe study of interaction and exchange among different geographic areas in the Western Pacific occupied by Lapita people (3500-2500 BP) has been an important component of research into the colonization process of the Pacific region. The Western Solomon Islands, lying in the central area of the Lapita distribution, have a unique archaeological record presenting intertidal sites with Late/Post Lapita ceramics as the only material evidence of Lapita occupation. Previous studies have indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…These results indicated that calcium, probably calcium carbonate (CaCO 3 ), was added to some potsherds to temper them in the clay‐making process, like a seashell, and different potsherds had different mixing rates. In past studies, the addition of calcium as a dilution effect for tempering was reported, and this characterized the pottery . These results suggest that mapping analysis was effected for visible identification of the size and quantity of particles in clay.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicated that calcium, probably calcium carbonate (CaCO 3 ), was added to some potsherds to temper them in the clay‐making process, like a seashell, and different potsherds had different mixing rates. In past studies, the addition of calcium as a dilution effect for tempering was reported, and this characterized the pottery . These results suggest that mapping analysis was effected for visible identification of the size and quantity of particles in clay.…”
Section: Resultsmentioning
confidence: 99%
“… However, these techniques are also destructive as they require thin samples, making it unsuitable for direct measurement of potsherd surface. Portable XRF enables nondestructive chemical analysis and is a useful instrument for on‐site field research of archeological material, but this method has problems arising from atmospheric conditions and manual measurement that negatively affect quantitativity and accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…(e.g., Hall, 2001; Li et al, 2008; Minc et al, 2016; Monette, Richer‐LaFlèche, Moussette, & Dufournier, 2007; Sherriff, Court, Johnston, & Stirling, 2002; Tschegg, Ntaflos, & Hein, 2009a; Vaughn & Neff, 2000). In Oceania, various pottery assemblages, from the earliest Lapita occupations (c. 3300–3200 BP) to much later traditions, have been the subject of compositional analysis involving collections from Mussau Islands (Hunt, 1989, 1993); Watom (Anson, 2000; Green & Anson, 1991, 2000); Manus (Ambrose, 1992, 1993; Ambrose, Duerden, & Bird, 1981); the Arawe Islands, West New Britain (Summerhayes, 2000); Buka Island, just north of Bougainville (Summerhayes, 1997); Papuan coastal areas such as Motupore Island on the southeastern coast of New Guinea (Rye & Duerden, 1982) and the Sepik Coast (Golitko, 2011) on the north side; Papuan islands of the Massim region (Shaw, Leclerc, Dickinson, Spriggs, & Summerhayes, 2016); Micronesia (Descantes, Neff, Glascock, & Dickinson, 2001); the Solomon Islands (Buhring, Azémard, & Sheppard, 2015; Tochilin et al, 2012); New Caledonia (Chiu, 2003a, 2003b, 2007); Vanuatu (Leclerc, ; Leclerc, Grono, Bedford, & Spriggs, ); Fiji (Bentley, 2000; Best, 1984; Clark & Kennett, 2009; Cochrane, 2004; Rutherford, Almond, & Nunn, 2012); Tonga (Burley & Dickinson, 2010); Samoa (Eckert & James, 2011); and a combination of samples from Fiji, Tonga and New Ireland (Kennett, Anderson, Cruz, Clark, & Summerhayes, 2004). The works of Allen and Rye (1982) in the Port Moresby area, Ambrose (1992, 1993) on Lapita pottery from Manus and Summerhayes (1997) on pottery from Buka, also documented clay properties and their effect on provenance studies.…”
Section: Introductionmentioning
confidence: 99%
“…Petrographic analysis indicates this was imported from Choiseul (Buhring et al . 2015; Nagaoka 2011: 178–183).…”
Section: Introductionmentioning
confidence: 99%
“…In support of the intertidal ceramic sites of New Georgia being representative of a colonisation phase, involving the transport of people and ideas from outside the archipelago, are a series of studies on the temper and fabric of the pottery (Buhring et al . 2015; Felgate & Dickinson 2001; Findlater et al . 2009).…”
Section: Introductionmentioning
confidence: 99%